The Effect of Organizational Culture and Self-Efficacy on Job Performance with Organizational Commitment as a Mediating Variable: A Study on Employees of PD X Jakarta - Dea Putri Nabilla; Corry Yohana; Christian Wiradendi Wolor (Journal of Management Economics and Financial Accounting, 2026)
This study aims to analyze the direct and indirect effects of organizational culture and self-efficacy on job performance, with organizational commitment serving as a mediating variable among employees at PD X Jakarta. A quantitative approach with a cross-sectional design was employed. The population comprised 200 employees, all of whom participated as respondents through a saturated sampling technique. Data were gathered using a structured questionnaire with a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0 software. The findings indicate that organizational culture has a positive and significant effect on job performance, with a path coefficient of 0.376, while self-efficacy also has a positive and significant effect on job performance, with a coefficient of 0.355. Furthermore, organizational culture positively and significantly influences organizational commitment (β = 0.585), and self-efficacy positively and significantly affects organizational commitment (β = 0.405). Additionally, organizational commitment exerts a positive and significant effect on job performance (β = 0.365). Indirect effect testing reveals that organizational commitment significantly mediates the relationship between organizational culture and job performance (β = 0.214), as well as between self-efficacy and job performance (β = 0.148), both exhibiting complementary partial mediation. The research model demonstrates strong explanatory power for job performance, with an R² value of 0.661, and moderate explanatory power for organizational commitment, with an R² value of 0.502. These findings emphasize that enhancing employee job performance requires an integrated human resource management strategy that strengthens organizational culture, fosters self-efficacy, and builds organizational commitment. Moreover, the SRMR value of 0.042 indicates an excellent model fit, confirming that the model possesses robust predictive quality in explaining variations in actual employee performance.